2006
DOI: 10.4314/eamj.v82i12.9382
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic ketoacidosis: risk factors, mechanisms and management strategies in sub-Saharan Africa: a review

Abstract: Diabetic ketoacidosis is the most common hyperglycaemic emergency in patients with diabetes mellitus, especially type 1 diabetes. It carries very high mortality in sub-Saharan Africa, both in the treated patients and those who are presenting to hospital with diabetes for the first time. Objective: To review the risk factors, mechanisms and management approaches in diabetes ketoacidosis in published literature and to discuss them in the context of why a significant proportion of patients who develop diabetic ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
56
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 0 publications
10
56
2
Order By: Relevance
“…So, healthcare professionals' alertness may need to be increased, particularly during certain months of the year. Polyuria, polydipsia, abdominal pain, vomiting, and altered level of consciousness were the commonest presenting complaints of DKA consistent with findings in previous studies (16,24).…”
Section: Discussionsupporting
confidence: 91%
“…So, healthcare professionals' alertness may need to be increased, particularly during certain months of the year. Polyuria, polydipsia, abdominal pain, vomiting, and altered level of consciousness were the commonest presenting complaints of DKA consistent with findings in previous studies (16,24).…”
Section: Discussionsupporting
confidence: 91%
“…DKA, in a resource limited setting such as Ghana, is diagnosed based on clinical features such as polyuria, polydipsia, polyphagia, weight loss, nausea, vomiting and abdominal pains, decreased loss of consciousness and weakness as well as biochemical evidence of hyperglycemia, usually >13.9 mmol/L, venous blood pH<7.3, bicarbonate <15 mmol/L, glycosuria, ketonemia and ketonuria [2][3][4]9]. Important investigations such as blood gases and blood ketones [2,9] are almost nonexistent at the district and regional hospitals of Ghana but may be restricted to some teaching hospitals where they are seldom being done due to lack of appropriate reagents.…”
Section: Discussionmentioning
confidence: 99%
“…Important investigations such as blood gases and blood ketones [2,9] are almost nonexistent at the district and regional hospitals of Ghana but may be restricted to some teaching hospitals where they are seldom being done due to lack of appropriate reagents. a combination of sensitive urinary pregnancy tests (UPT), transvaginal ultrasound (TVUSG) and serum hCG estimations and clinical features of vaginal bleeding, abdominal pains and vomiting [7,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Recent anthropological research from Cameroon also showed that obesity can be a deep-rooted status symbol. 12 Acute metabolic complications commonly develop in those with diabetes and these are associated with high mortality: 10-30% in diabetic ketoacidosis 13 and up to 41% in hyperglycaemic hyperosmolar non-ketotic coma (HONK). 14 These mortality rates are often caused by lack of insulin and delayed presentation.…”
Section: Lifestylementioning
confidence: 99%